2022
DOI: 10.1007/s11136-022-03110-5
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in cancer immunotherapy: a systematic perspective, using causal loop diagrams

Abstract: Purpose System science offers a unique set of tools, including causal loop diagrams (CLDs), for stakeholders to better grasp the complexity of factors surrounding quality of life. Because the health-related quality of life (HRQoL) of cancer immunotherapy patients exists within an intricate system affected by and affecting many factors across multiple dimensions, the development of a systems-level model can provide a powerful framework to aid the understanding of this complexity. We developed a CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Similar studies, also, have found a statistically significant association between socioeconomic and demographic characteristics and quality of life in cancer patients, such as marital status, age, and gender [ 22 - 25 ]. The present study highlights the severity of the disease but also the benefits of checkpoint inhibitor therapy on quality of life during and after treatment and is consistent with related studies [ 26 - 28 ]. However, a systematic study is needed at the national level in Greece to collect the necessary critical information on the course of the disease in cases monitored by hospitals in the country.…”
Section: Discussionsupporting
confidence: 92%
“…Similar studies, also, have found a statistically significant association between socioeconomic and demographic characteristics and quality of life in cancer patients, such as marital status, age, and gender [ 22 - 25 ]. The present study highlights the severity of the disease but also the benefits of checkpoint inhibitor therapy on quality of life during and after treatment and is consistent with related studies [ 26 - 28 ]. However, a systematic study is needed at the national level in Greece to collect the necessary critical information on the course of the disease in cases monitored by hospitals in the country.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies used system dynamics modeling as part of a mixed methods study in conjunction with other methods, such as mixed integer programming [33] or qualitative interviews and surveys [34]. People were the primary unit being modeled in 50% of the studies (n = 16) [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], while 16% modeled patient experience or behavior (n = 5) [50][51][52][53][54]. Other primary units modeled include cells (n = 4; 13%) [33, [55][56][57], environmental contaminants (n = 4; 13%) [58][59][60][61], currency (n = 2; 6%) [62,63], and web search queries (n = 1; 3%) [64].…”
Section: Plos Onementioning
confidence: 99%
“…Many studies included multiple diagrams to illustrate overall model structure or model subcomponents, while two studies did not include diagrams or descriptions of their model structure at all. Fig 2 illustrates examples of diagrams from two included studies, including a simplified causal-loop diagram related to cancer immunotherapy and patient quality of life [50], as well as a stockand-flow diagram corresponding to a simulation model of a Human Papillomavirus (HPV) vaccination program [43].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations